Anthropometric differences between world-class professional track cyclists based on specialty (endurance vs. sprint) - Muros, J.; Mateo-March, M.; Zabala, M.; Sánchez-Muñoz, C. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: Despite previous research suggesting that certain anthropometric characteristics are required to successfully perform in track cycling, current literature fails to describe these characteristics in depth in large cohorts of professional UCI cyclists. The main aims of the present study were to determine the anthropometric characteristics, body composition and somatotype of world-class professional track cyclists (male and female). METHODS: Anthropometric measurements were conducted of the body composition of ninety-eight world-class professional track cyclists in line with the International Society for Advancement of Kinanthropometry protocol. RESULTS: Male sprinters had a significantly larger body mass (85.9±8.3 vs. 74.0±6.5; P<0.001), muscle mass (44.1.9±4.4 vs. 35.3±2.5; P<0.001), body fat percentage (regardless of the formula used) and BMI (26.1±1.5 vs. 22.4±1.2; P<0.001) than endurance male cyclists. Furthermore, in females, sprinters had a higher BMI than endurance cyclists (23.4±2 vs. 1.4±1.6; P<0.01), with no differences in total body mass or body fat (P>0.05). None of the studied anthropometric parameters were found to differ between finalists and non-finalists, with the exception of femur breadth, upper arm girth, thigh girth and thigh skinfold. CONCLUSIONS: Intra-sport differences exist in the anthropometric characteristics of world-class professional track cyclists depending on their discipline (sprinter vs. endurance). Male sprinters showed a greater BMI, muscle mass and limb girth, and lower fat percentage than endurance cyclists. Female sprinters also showed a higher BMI than endurance cyclists, although no differences were seen in fat percentage or muscle mass.